The Cultural Outcomes of Social Movements: A Computational Linguistics Approach - Camilo Cristancho (Coordinamento SIBA, 2021)
Scholars have long established the importance of the cultural outcomes of social movements in the context of political power and representation. However, they have also acknowledged the methodo-logical difficulties associated with studying cultural outcomes, especially when culture is manifested through linguistic practices. This paper addresses the potential for dealing with movements and culture as mani-fested in symbols, public discourse, narratives, and rhetoric and makes two contributions: It links the social movement literature studying culture through language with Natural Language Processing (NLP) techniques for systematic and comprehensive cultural analysis; and introduces a state-of the-art method which pro-vides a better understanding of language change and linguistic influence given the capacity of computa-tional analyses to process large volumes of data for multiple actors and varied data sources during long pe-riods of time. The paper describes the cultural influence of women organizations in Spain between 2000-2020 on issues such as gender inequalities, abortion, gender violence, prostitution, and surrogacy. Tweets and manifestos by women's organizations', as well as national press coverage of women issues and inter-ventions by MPs in the parliamentary arena, are used to describe the advantages and limitations of the method for the study of cultural outcomes. Computational linguistics provides new possibilities for scholarly research on cultural outcomes of social movements but also shows that these methods should be accompa-nied by precise definitions of cultural outcomes, detailed and replicable operationalisation processes, and theoretical models that identify the mechanisms that explain the linguistic phenomena that underly cultural change.